2015
DOI: 10.17221/8582-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of body weight and bone weight with densitometric properties of tibiotarsal bone in geese during post-hatching development

Abstract: ABSTRACT:The aim of this study was to evaluate interrelationships of body weight and bone weight and densitometric properties of the tibiotarsus in White Koluda Geese (W31) in the post-hatching period. The study was performed using dual-energy X-ray absorptiometry (DEXA) and peripheral quantitative computed tomography (pQCT) at two different parts of tibia: proximal metaphysis and mid-diaphysis. The investigation was performed on 100 bones obtained from males and females at the age of 1, 14, 28, 42 and 56 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Williams et al [7] reported that fast-growing broilers had a faster bone deposition at the periosteal surface than slow-growing broilers, which was associated with decreased mineralization, increased cortical porosity, and altered biomechanical properties. In the production of meat geese, deformations and fractures of the tibiotarsal bones also occur frequently [8]. To improve bone quality in geese, it is essential to know the structure of the bone tissue in postnatal development in geese.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al [7] reported that fast-growing broilers had a faster bone deposition at the periosteal surface than slow-growing broilers, which was associated with decreased mineralization, increased cortical porosity, and altered biomechanical properties. In the production of meat geese, deformations and fractures of the tibiotarsal bones also occur frequently [8]. To improve bone quality in geese, it is essential to know the structure of the bone tissue in postnatal development in geese.…”
Section: Introductionmentioning
confidence: 99%